PERAN MANAJEMEN STRATEGIK DALAM PENGEMBANGAN KURIKULUM BERBASIS NILAI-NILAI ISLAM - Setiawan, Deny; Fathurrahman; Hidayat, Ara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the role of strategic management in developing an Islamic values-based curriculum in Islamic educational institutions. The findings reveal that the systematic and effective implementation of strategic management significantly enhances the quality of Islamic education through strategic planning, directed implementation, and continuous evaluation. The study highlights the importance of involving all stakeholders, such as teachers, parents, and communities, to ensure the successful implementation of the curriculum. Despite challenges like resistance to change and limited resources, the study recommends utilizing technology and conducting socialization efforts to support better curriculum development. This research provides practical and theoretical contributions to the development of Islamic education management, particularly in the digital era. Keywords: strategic management, curriculum, Islamic values, Islamic education, curriculum evaluation